BIANCHI TYPE-II RENYI HOLOGRAPHIC DARK ENERGY MODEL IN SAEZ-BALLESTER THEORY OF GRAVITY (International Journal of Mathematics and Physics, 2025)
In Saez-Ballester's (Physics Letters A: 113, 467, 1986) theory of gravitation, the paper presents the study of Bianchi type-  interacting Rényi holographic dark energy determined. We determine interacting dark energy models by considering a correlation between the metric potentials to solve the field equations of the model. This results in a dynamical deceleration parameter which demonstrates a shift in the cosmic rate of acceleration from deceleration to acceleration, with a redshift  change that is compatible with observations. Despite assuming several values to parameters  close to  at  (the present epoch) and is in agreement with the most recent observations. Next, we discovered that the squared sound speed, , is negative at the initial epoch and positive at the present epoch, implying instability against perturbations at the initial epoch and stable at the present epoch. The -  plane is constructed to investigate the evolution of the models’ EoS parameter turned out to be in the freezing zone. As should be the case in an expanding universe, the strong energy conditions of the models are violated. Statefinders  plane confirms that our model includes the Chaplygin gas, phantom and  limit.Keywords: LRS Bianchi type-  metric, Saez-Ballester theory, Rényi holographic dark energy, scalar-tensor theory, cosmology.